Population genomics of Plasmodium vivax in Panama to assess the risk of case importation on malaria elimination - Buyon, Lucas E.; Santamaria, Ana Maria; Early, Angela M.; Quijada, Mario; Barahona, Itza; Lasso, Jose; Avila, Mario; Volkman, Sarah K.; Marti, Matthias; Neafsey, Daniel E.; Obaldia III, Nicanor (PLOS Neglected Tropical Diseases, 2020)
Author summary Plasmodium vivax is a major global health threat particularly in Central and South America which experiences 700,000 P. vivax cases each year. Panama has greatly reduced P. vivax incidence, however, this progress has since plateaued. Understanding how the parasite moves throughout the country, uncovering pockets of focalized transmission, and identifying imported cases, is critical for Panama and other countries to succeed in their elimination efforts. Genomic epidemiology and population genomics tools can help provide this information needed to inform malaria control policy. In this study, we collected 100 Panamanian P. vivax samples from two time periods (2007–2009 and 2017–2019), of which 59 yielded usable sequencing data. We found that the majority (n = 47) samples belong to a single highly related lineage, termed CL1. This lineage has persisted since at least 2007. We also observed a second smaller completely clonal lineage of four parasites, termed CL2. Additionally, we observed four samples that shared no recent ancestry with any other Panamanian samples but clustered with samples collected in a previous study from Colombia. We highlight how genomic epidemiology can be used to spotlight parasites that may be imported as a result of human migration, as well as corroborate or refute the country of origin as suggested by the travel history of a patient. There is no evidence of outcrossing between these potentially imported parasites and the local Panamanian parasite population. This finding suggests that imported parasites are not driving ongoing malaria transmission in Panama. We note the need for sustained genomic surveillance of P. vivax in Panama to monitor transmission dynamics in the local population and to further flag potentially imported cases. The low diversity we observe in Panama indicates that this parasite population has been previously subject to a severe bottleneck and may be eligible for elimination.